Pre–Post Evaluation of a Community-Based Sleep Training Program for Older Men with Sleep Disorders in Duhok Governorate - Iman Mohammed Mustafa; Shireen Safar Mousa (Jurnal Theologia, 2026)
Sleep disorders are a common health concern among older adults and are often associated with reduced physical functioning, impaired cognition, and poorer psychological well-being. This study aimed to conduct a pre–post evaluation of a community-based sleep training program for older men with sleep disorders in Duhok Governorate, Iraq. A single-group pretest–posttest design was employed involving 10 community-dwelling men aged 60–63 years who reported sleep-related difficulties. Participants attended an 8-session training program delivered over four weeks in a community setting. The intervention included sleep hygiene education, relaxation techniques, behavioral strategies, and practical guidance to improve sleep-related habits. Outcome assessment was conducted before and after the intervention using the Pittsburgh Sleep Quality Index (PSQI) as the primary measure, supported by selected indicators of sleep pattern and daytime functioning. The findings showed improvement in overall sleep quality following participation in the program, reflected in lower PSQI scores, reduced sleep onset latency, improved sleep efficiency, and longer total sleep duration. Positive changes were also observed in daytime sleepiness and selected cognitive functioning outcomes. These findings suggest that a structured community-based sleep training program may provide short-term benefits for older men experiencing sleep disturbances. However, the results should be interpreted cautiously, given the small sample size, absence of a control group, and limited follow-up period. Further controlled studies with larger samples are needed to confirm the intervention's effectiveness and generalizability